(untitled) (Global Journal of Medical Research, 2012)
A randomized study was carried out to determine the changes during the growth period in 1-6 years groups. The study consists of 350 children from different slum in Bijapur city. The different parameters were measured and compared with national centre for Chronic Disease prevention and health promotion Committee 2000(CDC) standards. Most of the parameters like Height, Weight and Head circumference were reduced significantly in Study groups in comparison to CDC standards in both sexes. The Significant change in the values of different parameters in Study group may be due to illiteracy, poor sanitation and nutrition etc.